2019
DOI: 10.3390/app9173464
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Properties of Zirconia Nanoparticles and Chitosan-Based Intumescent Flame Retardant Coatings

Abstract: Zirconia (ZrO2)-based flame retardant coatings were synthesized through the process of grinding, mixing, and curing. The flame retardant coatings reinforced with zirconia nanoparticles (ZrO2 NPs) were prepared at four different formulation levels marked by F0 (without adding ZrO2 NPs), F1 (1% w/w ZrO2 NPs), F2 (2% w/w ZrO2 NPs), and F3 (3% w/w ZrO2 NPs) in combination with epoxy resin, ammonium polyphosphate, boric acid, chitosan, and melamine. The prepared formulated coatings were characterized by flammabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 51 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…The LOI and UL-94 V results revealed that the optimum amount of ZnO was 3%. The TGA data clearly indicated that the addition of ZnO can greatly increase the thermal stability of the coating by increasing the char residue percentage at high temperature [36,37]. APP and ETPMP can easily participate in phosphor esterification reaction at their decomposition temperatures, as ETPMP has a significant number of -OH groups.…”
Section: Discussionmentioning
confidence: 99%
“…The LOI and UL-94 V results revealed that the optimum amount of ZnO was 3%. The TGA data clearly indicated that the addition of ZnO can greatly increase the thermal stability of the coating by increasing the char residue percentage at high temperature [36,37]. APP and ETPMP can easily participate in phosphor esterification reaction at their decomposition temperatures, as ETPMP has a significant number of -OH groups.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1(c) represents the FT-IR spectrum of ZrO 2 , and the peaks appeared at around 1052 cm −1 and 793 cm −1 are assigned to the absorption of monoclinic Zr-O bond. Moreover, a peak below 650 cm −1 is ascribed to the vibration modes of the ZrO 3 −2 group [21]. Figure 1(d) represents the FT-IR spectrum of V 2 O 5 , and the peaks that appeared below 1200 cm −1 are attributed to the characteristic vibration bands of V-O [22].…”
Section: Resultsmentioning
confidence: 96%
“…The FTIR spectra of the calcined fibers show only bending and stretching vibrations of -OH groups originating from coordinated or readsorbed water at 3300, 1575 and 1405 cm −1 and Zr-O vibrations at 750 cm -1 and below 500 cm -1 . [14,40,41] The absence of IR peaks of organic groups confirms the purity of the synthesized products that is essential for the uptake properties of the material as organic residues could cover active surface sites of ZrO 2 .…”
Section: Tgamentioning
confidence: 83%